2020
DOI: 10.3389/fpsyg.2020.568382
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Mental Rotation in Preschoolers With High or Low Working Memory Capacity: An fNIRS Study

Abstract: This study explored the differentiated neural correlates of mental rotation (MR) in preschoolers with high and low working memory capacity using functional near-infrared spectroscopy (fNIRS). Altogether 38 Chinese preschoolers (M = 5.0 years, SD = 0.69 years) completed the Working Memory Capacity (WMC) test, the Mental Rotation (MR), and its Control tasks (without MR). They were divided into High-WMC (N1 = 9) and Low-WMC (N2 = 18) groups based on the WMC scores. The behavioral and fNIRS results indicated that:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
1
1
Order By: Relevance
“…Generally speaking, children have a problem with this skill (e.g., Mix et al, 2018;Newcombe et al, 2018). Our results on Mental Rotation tasks do not match the results on the same tasks for preschoolers in Yang et al (2020). However, the mixed findings about spatial scaling skill and mental rotation skill put us in a position of questioning.…”
Section: Discussioncontrasting
confidence: 81%
“…Generally speaking, children have a problem with this skill (e.g., Mix et al, 2018;Newcombe et al, 2018). Our results on Mental Rotation tasks do not match the results on the same tasks for preschoolers in Yang et al (2020). However, the mixed findings about spatial scaling skill and mental rotation skill put us in a position of questioning.…”
Section: Discussioncontrasting
confidence: 81%
“…Studies have shown that fNIRS can effectively monitor cortical haemodynamics during spatial memory tasks 28 . The prefrontal lobes are significantly activated during spatial working memory tasks 29 . The dorsolateral prefrontal cortex (DLPFC), among others, has been identified as a potential brain target for fNIRS neurofeedback to enhance spatial memory in humans 30 .…”
Section: Introductionmentioning
confidence: 99%